包含至少个优选地是透明的图案的半透明玻璃板 (2018)
本发明涉及玻璃板，优选地半透明的玻璃板，包含至少个图案，优选地透明图案，并且涉及用于制备这种玻璃板的方法。该玻璃板包含具有两个主要外表面的基材，所述外表面的至少个是纹理化表面，该基材由具有折光指数n的电介质材料构成，该基材的纹理化表面的至少部分用溶胶-凝胶层涂覆，该溶胶-凝胶层由具有折光指数n的电介质材料组成。 A glazing, which may be translucent, includes at least one design, which may be transparent. The glazing includes a substrate having two main outer surfaces, at least one of which is a textured surface, made of a dielectric material having a refractive index n1 and at least a part of the textured surface of the substrate is coated with a sol-gel layer made of a dielectric material having a refractive index n2.